Multilateral treaty framework : an invitation to universal participation : focus 2004 : treaties on the protection of civilians (UN New YorkUS, 2004)
Presents treaties that have been adopted by the international community with regard to the protection of civilians in conflict situations.
Keywords: HUMAN RIGHTS